Virtual Research Environments: Overview and Activity (UKOLN, 2005)
Virtual research environments (VREs) comprise digital infrastructure and services which enable research to take place. The idea of a VRE, which in this context includes cyberinfrastructure and e-infrastructure, arises from and remains intrinsically linked with, the development of e-science. The VRE helps to broaden the popular definition of e-science from grid-based distributed computing for scientists with huge amounts of data to the development of online tools, content, and middleware within a coherent framework for all disciplines and all types of research. This article highlights some of the issues relating to the development and deployment of VREs and introduces three VRE projects in which Oxford University is leading or playing a significant role.